THE CORRELATION BETWEEN STUDENTS’ READING HABIT AND THEIR READING COMPREHENSION - Fitri Dewi Sartika; Nurul Afifah; Yentri Anggraini (BASIS (Bahasa dan Sastra Inggris), 2020)
The aim of this study was to observe on the correlation between students’ reading habit and their reading comprehension of eleventh grade at SMA Negeri 1 Madang Suku 3 OKU Timur. In this quantitative study with correlational study, the writer used questionnaire and test to collect the data. The questionnaire measured students’ reading habit and test measured students’ reading comprehension. Populationof this study was all the eleventh grade students of SMA Negeri 1 Madang Suku 3 OKU Timur in academic year 2018/2019 were 124 student and took sample by using purposive sampling were 64 students. Based on the finding, the mean score of questionnaire was 60,89 and mean score of students’ reading comprehension was 56,94 which was in moderated category. The writer found that there was significantly correlation between students’reading habit and their reading comprehension the correlation coofficient was 0,555. It meant that alternative hypothesis (Ha) was accepted and null hypothesis was rejected in other word there was any significant correlation between students’ reading habit and their reading comprehendion in medium correlation. As the conclusion,reading habit was not only aspect that influenced strudent reading comprehension that many factor also influenced the reading comprehension: internal factor (intellectual, language skills, psychological, environment, experience) and external factor (facilities, time to learning).To have good reading comprehension the student should know aspects reading comprehension were ability of association, conception ability, perception ability, syntactic ability - semantic ability and cognitive understanding.